The New Vitality of Salafism in Côte d’Ivoire: Toward a Radicalization of Ivoirian Islam? - Madore, Frédérick (2016)
This article examines recent developments of Salafism in Côte d’Ivoire by exploring how the movement has evolved over the last 25 years through its main national associations and leaders. Although the situation with regard to terrorism has changed in this country since the attack in Grand-Bassam on 13 March 2016, the intent of this article is to move beyond a reductive focus on security and counterterrorism by painting a more-nuanced portrait of one local manifestation of a global movement often reduced to violence and conflict. Far from becoming radicalized and despite increasing levels of activism, the country’s Salafi elites and main national associations have demonstrated civic engagement and opposition to terrorism. They also increased their participation in the socioeconomic arena as well as their willingness to act as a key intermediary between the Muslim community and the country’s political leadership.
Keywords: Islam -- Salafism -- Wahhabism -- terrorism -- Côte d’Ivoire -- Ivory Coast